Improving prosthetic prognosis by connective tissue ridge augmentation of alveolar ridge - Mishra Niraj; Singh Balendra; Rao Jitendra; Rastogi Pavitra (Wolters Kluwer Medknow Publications, 2010)
The contour of edentulous ridge should be carefully evaluated before a fixed partial denture is undertaken. The ideal ridge height and width allows placement of a natural looking pontic which facilitates maintenance of plaque-free environment. The localized alveolar ridge defect refers to the volumetric deficit of the limited extent of bone and soft tissue within the alveolar process. Such type of ridge defects can be corrected by surgical ridge augmentation that can be accomplished by the addition of either soft or hard tissues. This article describes a procedure of surgical connective tissue augmentation of a localized deficient alveolar ridge in the maxilla, followed by fixed partial denture, enhancing the esthetics, function and health.